A Flow Electrochemical Cell with Split Bipolar Electrode for Anodic Oxidation of Organic Compounds. Issue 6 (16th March 2022) - Sakagami, Hiroki; Takenaka, Hiroaki; Iwai, Suguru; Shida, Naoki; Villani, Elena; Gotou, Akihiro; Isogai, Tomohiro; Yamauchi, Akiyoshi; Kishikawa, Yosuke; Fuchigami, Toshio; Tomita, Ikuyoshi; Inagi, Shinsuke
Abstract: The recent development of flow electrochemical reactors has been remarkable, but efforts are still required to reduce the amount of supporting electrolyte used in electrosynthesis. To address this problem, herein an advanced process combining flow reactors and bipolar electrochemistry is proposed. The developed electrochemical system was successfully employed for the anodic fluorination and anodic coupling of organic compounds using low concentration of supporting electrolytes. Such combined electrochemical system would represent a promising electrosynthesis method toward green and sustainable chemistry. Abstract : Flowing to success : A novel flow electrochemical reactor with a split bipolar electrode (BPE) is developed to achieve anodic fluorination and coupling of organic compounds using low concentration of supporting electrolytes.